Crystallising the official narrative: News discourses about the killings from the Philippine government’s campaign against illegal drugs - Soriano, Cheryll Ruth R (Archīum Ateneo, 2019)
News media’s construction of crime and drugs can shape and change public perceptions and influence popular acceptance of policy and state responses. In this way, media, through selection of sources and framing of narratives, act as important agents of social control, either independently or indirectly by state actors. This article examines how the Philippine government’s anti-drug campaign, and the thousands of deaths resulting from them, has been depicted by the media to the public. We conducted a discourse analysis of television news stories to extract dominant frames and narratives, finding a pattern of over-privileging of State authority as a source, resulting in a monolithic message of justifying the killing of suspects. Furthermore, the ‘event-focused’ slant, which dominates the character of reports by media, inevitably solidifies the narrative that the deaths are a necessary consequence of a national public safety campaign. By relying almost exclusively on this narrative, to the exclusion of alternative frames, the media amplifies and crystallises the state’s narrative. As we critically examine how drugs, drug use and the zero-tolerance policy are positioned through discourse in news texts, the article raises important implications to the ethics and role of journalism in politics and provides explanations relating to crime-reporting norms, values and media organisation realities in the country.